Aerodynamic analysis on postures of ski jumpers during flight using computational fluid dynamics - Ryu, M.; Cho, L.; Cho, J. (Transactions of the Japan Society for aeronautical and space sciences, 2015)
The aerodynamic characteristics of a ski jumper model in various postures are analyzed using a commercial computational fluid dynamics tool. The purpose of this study is to understand the aerodynamic characteristics of ski jumping. The range of flying postures for ski jumpers is determined as widely as possible to simulate the optimal flight position of ski jumpers. The computational results are in good agreement with experimental results. The aerodynamic characteristics are influenced by the hip and body angles of the ski jumper model during the flight. The lift-to-drag ratio of ski jumpers is increased as hip angle increases. However, as the hip angle increases, the region of the angle of attack becomes restricted for stable flight. The augmentation of the body angle can enhance the most favorable angle of attack, because the body angle is likely to result in a cambered airfoil. In conclusion, the ski jumper should maintain a high hip angle with an angle of attack that stabilizes the flight condition, to improve flight distance.